2022
DOI: 10.3390/agronomy12040970
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment Framework to Analyze Drought Management Plans: The Case of Spain

Abstract: Droughts affect all socio-economic sectors and have negative impacts on the environment. Droughts are expected to increase in frequency and severity due to climate change, which makes their effective management a high priority for policy makers and water managers. Drought Management Plans (DMPs) are a key instrument to deal with droughts and help to prepare for them in a proactive way as a framework for coordinated action before and during droughts. The development of DMPs is still incipient worldwide and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Some studies showed that due to the intensification of global climate change, such as a significant decrease in precipitation but a simultaneous increase in temperature [ 52 ], the frequency, intensity, and scope of influence of drought were increasing [ 53 , 54 ]. For instance, the southwest China extreme drought in 2010 [ 55 ], the 2010–2013 southern United States drought [ 56 ], and the severe drought problems in the Mediterranean area [ 57 , 58 ]. Therefore, climate change might be a main driving force that affects the hydrological cycle [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies showed that due to the intensification of global climate change, such as a significant decrease in precipitation but a simultaneous increase in temperature [ 52 ], the frequency, intensity, and scope of influence of drought were increasing [ 53 , 54 ]. For instance, the southwest China extreme drought in 2010 [ 55 ], the 2010–2013 southern United States drought [ 56 ], and the severe drought problems in the Mediterranean area [ 57 , 58 ]. Therefore, climate change might be a main driving force that affects the hydrological cycle [ 52 ].…”
Section: Resultsmentioning
confidence: 99%